A review of emerging trends in experimental, simulation, and theoretical methods for dose calculation in radiation processing - Firmansyah Okky A.; Kurniawan Budhy; Saputro Bimo; Walo Marta; Gryczka Urszula; Nuraeni Nunung (Nukleonika)
Dosimetry serves as the backbone of ionizing radiation treatment in radiation processing, ensuring precision and accuracy in transferring the absorbed dose for medical sterilization and phytosanitary applications. Over the years, methods for calculating and measuring the absorbed dose have significantly advanced. Although experimental dosimetry remains indispensable, simulation techniques – such as Monte Carlo (MC) methods – have gained prominence by providing deeper insights into the physical processes of radiation interactions. Additionally, theoretical methods continue to provide accurate dose calculations, contributing to the field’s progress. This study examines recent advancements in dose calculation techniques for radiation processing, highlighting individual methods – experimental, simulation-based, and theoretical – as well as their combinations to achieve accurate and reproducible dose measurements. It also addresses the challenges associated with each radiation processing method and discusses future prospects for improving the dosimetry of radiation processing techniques.